The Chestnut Soldier - Nimmo, Jenny (New York : Orchard Books, 2007)
To purge the anger from an ancient Welsh demonic god that he had helped release, and to soothe a moody, troubled soldier, Gwyn Griffiths draws on the strength of his namesake and ancestor in Welsh magic, Gwydion Gwyn.
The magican trilogy ; book three.
Keywords: Magic